BRIDGING THE GAP BETWEEN AGRICULTURAL ENGINEERING EDUCATION AND POLICY IMPLEMENTATION IN NIGERIA - Buba, B. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The agricultural engineering education system in Nigeria fails to provide necessary skills for agricultural development because it operates separately from actual government work. Universities produce graduates who know theoretical concepts but the lack of effective links to government policies prevents them from using their knowledge in actual agricultural settings. The research examines institutional structural and policy barriers which create this gap between educational systems and policy frameworks. The research used qualitative methods to conduct policy analysis and stakeholder assessment and institutional evaluation which revealed problems related to poor funding and weak collaboration and lack of industry ties and obsolete educational programs. The research shows that the disconnect between education and work training leads to high unemployment rates among graduates and low use of mechanized farming methods and ineffective farming methods. The proposed framework requires universities and government agencies and private sector partners to work together on developing curriculum based on policy needs while improving internship opportunities and creating better systems for sharing knowledge. The study concluded that Nigeria needs to close its education-policy gap in order to achieve agricultural development and food security and sustainable rural growth. To address these challenges, it is recommended that stronger institutional partnerships be established between universities, government bodies, and industry stakeholders to ensure alignment between educational outputs and national agricultural priorities. Additionally, there is a need to modernize agricultural engineering curricula by integrating practical training, digital technologies, and entrepreneurship to equip graduates with relevant and applicable skills for the evolving agricultural sector.